High rates of sexually transmitted infections in HIV positive homosexual men: data from two community based cohorts. Issue 5 (7th June 2007) - Jin, Fengyi; Prestage, Garrett P; Zablotska, Iryna; Rawstorne, Patrick; Kippax, Susan C; Donovan, Basil; Cunningham, Philip H; Templeton, David J; Kaldor, John M; Grulich, Andrew E
Abstract : Background/objectives: Higher levels of sexual risk behaviours have been reported in HIV positive than in HIV negative homosexual men. In clinic based studies, higher rates of sexually transmitted infections (STIs) have also been reported. We compared rates of common STIs between HIV positive and HIV negative homosexual men from two ongoing community based cohort studies in Sydney, Australia. Methods: Participants in the two cohorts were recruited using similar community based strategies. They were interviewed face to face annually after enrolment. Comprehensive sexual health screening, including hepatitis A and B, syphilis, gonorrhoea, and chlamydia (in urethra and anus) was offered to participants in both cohorts. Results: In participants in the HIV positive cohort, 75% were hepatitis A seropositive, 56% had serological evidence of previous or current hepatitis B infection, and 24% had evidence of vaccination against hepatitis B infection. 19% of men tested positive for syphilis and 4% had evidence of recent infections. Compared with men in the HIV negative cohort, after adjustment for age, HIV positive participants had significantly higher prevalence of previous or current hepatitis B infection, syphilis, and anal gonorrhoea. Conclusion: This finding supports the need for frequent STI testing in HIV positive men to prevent morbidity and to decrease the risk of ongoing HIV transmission.